Molecular detection of tick-borne rickettsial and protozoan pathogens in domestic dogs from Turkey - Aktas M, Özübek S, İpek Nds, Altay K, Balkaya I, Utuk Ae, Kırbas A, Şimsek S, Dumanlı N (My University, 2015)
Background: Canine tick-borne parasites have emerged in recent years, showing a wider geographic distribution and increased global prevalence. In addition to their veterinary importance, domestic dogs play an important role in the transmission cycles of some agents by acting as reservoirs and sentinels. This study investigated Babesia, Theileria, Anaplasma, and Ehrlichia species in asymptomatic dogs in ten provinces of Turkey. Methods: DNA obtained from blood samples collected from 757 domestic dogs (243 stray, 351 shelter, 163 pet) of both sexes and various ages were evaluated using PCR and reverse line blotting (RLB) assays. Results: Of the 757 dogs tested, 41 (5.4%) were found to be infected with one or more parasites. Ehrlichia canis (37/757, 4.9%) was the most common canine tick-borne pathogen, followed by Anaplasma platys (4/757, 0.5%). Babesia canis and Theileria annulata were each detected in 1 (0.13%) sample. Combined infection of E. canis and A. platys was detected in 2 (0.3%) samples. The prevalence of tick-borne pathogens was higher in adult dogs (6.8%) than in those under one year old (3.1%). Difference in infection rate of male and female dogs was not significant. Pet dogs had a lower prevalence of infection (1.2%) compared to stray (7.4%) and shelter dogs (6%) although the difference between stray and shelter dogs was not significant. Conclusions: Babesia canis, T. annulata, A. platys, and E. canis species were identified at the molecular level in dogs in several provinces of Turkey, with E. canis being the most common species among tick-borne pathogens. Detailed studies should be conducted regarding the existence and prevalence of B. canis and Dermacentor reticulatus in eastern Turkey.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Dog; Babesia canis canis; Anaplasma platys; Ehrlichia canis; Theileria annulata; RLB